PENGARUH GENOTIP DAN PUPUK KANDANG TERHADAP PERTUMBUHAN DAN PRODUKSI KEDELAI PANEN MUDA DI LAHAN KERING - Munif Ghulamahdi; - Nuraeni (Agrovigor, 2009)
The objective of this experiment was to determine of dung fertilizer dosage on two soybean genotypes on dry land. The experiment was conducted in IPB Experimental Station Cikarawang, Bogor, from April to June 2001. This experiment used split plot design with three replication. The mainplot was genotypes consisted of : NS (Nakorn Sawan), and G (Genotype)  10428; and the subplot was dung fertilizer dosage consisted of : 0, 1, 2, 4 ton/ha.   The genotype effected to the stalk dry weight at 4 WAP (Week After Planting), and fresh pod weight per plot The dung fertilizer dosage only effected to the number of fill pod per plant,  and the interaction did not effect to the all variables.